2023
DOI: 10.26668/businessreview/2023.v8i5.2101
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hrm Practices, Transformational Leadership and Organization Commitment on Employee Performance at the Ministry of Agriculture and Fisheries in Oman the Moderating Role of Organizational Justice

Abstract: Purpose:  The purpose of this article is to examine the impact of HRM practices, transformational leadership, and organizational commitment on employee performance in the Ministry of Agriculture and Fisheries in Oman, as well as the moderating role of organizational justice in this relationship.   Theoretical framework: This study integrates theoretical perspectives on HRM practices, transformational leadership, organizational commitment, organizational justice, and employee performance. It posits that HRM pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In accordance with the main purpose of knowledge sharing between employees, namely to transfer knowledge into organizational assets and resources. This is in line with research conducted by Vizano et al (2020); Sunarsi et al (2020); Hubais et al (2023) where individual willingness to share knowledge allows organizations to promote innovative work behavior. Furthermore Sanguanwongs (2023) also confirms that knowledge sharing has significant power and impact on employee innovative behavior.…”
Section: The Effect Of Knowledge Sharing On Innovative Worksupporting
confidence: 91%
“…In accordance with the main purpose of knowledge sharing between employees, namely to transfer knowledge into organizational assets and resources. This is in line with research conducted by Vizano et al (2020); Sunarsi et al (2020); Hubais et al (2023) where individual willingness to share knowledge allows organizations to promote innovative work behavior. Furthermore Sanguanwongs (2023) also confirms that knowledge sharing has significant power and impact on employee innovative behavior.…”
Section: The Effect Of Knowledge Sharing On Innovative Worksupporting
confidence: 91%
“…This leadership style fosters self-confidence, optimism, and commitment among employees, leading to better performance (Udin, 2023). The relationship between transformational leadership and employee performance is mediated by factors such as relational identification with the supervisor, self-efficacy, trust, and organizational commitment (Hubais et al, 2023;Yuan et al, 2017). These indirect interrelations are crucial for enhancing employee performance, as they help create a positive work environment and motivate employees to excel in their roles (Pamungkas et al, 2023).…”
Section: Literature Review and Hypothesis Development A Job Satisfactionmentioning
confidence: 99%
“…Similarly, (Alenzi et al, 2023) examined the influence of green human resource management practices on sustainable performance and how GHRM practices can help Qatari organizations to improve their environmental performance through organisational sustainability and employee behaviour. In the same context, the impact of HRM practices, transformational leadership, and organisational commitment on employee performance was investigated and it was revealed that HRM practices have a significant impact on employee performance and thus affect organisational performance (Huabis, et al 2023).…”
Section: Hrm Practicesmentioning
confidence: 99%